The effect of maximal electroshock seizure and anticonvulsants on the concentration of lipid peroxidation products in an experiment in mice - I. O. Gaydukov; S. A. Litvinova; N. N. Zolotov; S. O. Kotelnikova; T. A. Voronina (LLC "Publisher OKI", 2022)
Oxidative stress plays a key role in epileptogenesis. The aim of the study was to evaluate the effect of seizures on the development of oxidative stress and the presence of antioxidant properties in carbamazepine and valproic acid in convulsive state caused by maximal electroshock seizure (MES). Methods. An electroconvulsive seizure were induced by the MES-test in mice, with assessment of the severity of seizures on a point scale. Oxidative stress was assessed by products of lipid peroxidation (LPO) determined in blood plasma. Results. It has been established that exposure to MES followed by tonic-clonic seizures leads to oxidative stress in mice. Valproic acid and carbamazepine completely protected against seizures after MES-test, however, the concentration of lipid peroxidation products did not differ from the MES group and was also higher than in the control group.